Roles of Ti in Electrode Materials for Sodium-Ion Batteries - Wang, Yuesheng; Zhu, Wen; Guerfi, Abdelbast; Kim, Chisu; Zaghib, Karim (Frontiers in Energy Research, 2019)
Sodium-ion batteries offer a promising alternative to lithium-ion batteries due to their low cost, environmental friendliness, high abundance of sodium, and established electrochemical process. However, problems, such as low capacity, low storage voltage and capacity fade of electrode materials, must be resolved for the applications of sodium ion batteries. Many Ti-containing compounds were reported as cathode and anode materials, but very few studies focus on the role of Ti in electrodes used in sodium-ion batteries. This paper systemically reviews the roles of Ti in electrodes of sodium ion batteries. The Ti4+/Ti3+ redox couple is a good choice for anodes due to its low potential and it exhibits different storage voltages in different structures. Although Ti4+ does not participate in charge transfer in cathodes, it can indirectly enhance the capacity, cycling life and rate performance via structure change, cation order-disorder transition, and its interaction with the crystal lattice structure. This review will provide a new insight in designing and understanding novel high-performance electrodes.